2023
DOI: 10.1007/s00018-022-04683-7
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive autophagy reprogramming in Schwann cells during peripheral demyelination

Abstract: The myelin sheath is an essential structure for the rapid transmission of electrical impulses through axons, and peripheral myelination is a well-programmed postnatal process of Schwann cells (SCs), the myelin-forming peripheral glia. SCs transdifferentiate into demyelinating SCs (DSCs) to remove the myelin sheath during Wallerian degeneration after axonal injury and demyelinating neuropathies, and macrophages are responsible for the degradation of myelin under both conditions. In this study, the mechanism by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…It has been shown that demyelinating SCs during Wallerian demyelination after axonal injury utilize autophagy for myelin clearance 22 24 . We recently reported that demyelinating SCs in Wallerian demyelination employ autophagy machineries for excreting degenerating myelin and that p62 secretion from SCs could be an index of such demyelination activity of SCs 25 , 26 . Those reports further support our hypothesis of the potential SC source of plasma p62 elevation in patients with demyelinating CMT.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that demyelinating SCs during Wallerian demyelination after axonal injury utilize autophagy for myelin clearance 22 24 . We recently reported that demyelinating SCs in Wallerian demyelination employ autophagy machineries for excreting degenerating myelin and that p62 secretion from SCs could be an index of such demyelination activity of SCs 25 , 26 . Those reports further support our hypothesis of the potential SC source of plasma p62 elevation in patients with demyelinating CMT.…”
Section: Discussionmentioning
confidence: 99%
“…ATG1, ATG13, and ATG17 expression products so combine to create the autophagy initiation complex (ULK1 complex) (Gao et al 2019). The demyelinating Schwann cells seemed to utilize myelin membranes for secretory phagophore formation and employed p62/sequestosome-1 (p62) as an autophagy receptor for myelin excretion (Jo et al 2023). LC3 precursors form after protease process LC3-I.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, Wallerian degeneration of the distal nerve stumps occurs immediately after peripheral nerve injury 40,41 . In Wallerian degeneration, the damaged myelin sheath and axon fragments are removed, and a microenvironment suitable for the regrowth of axons is formed in the wound area, which is a key process of peripheral nerve regeneration 25,42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…Wallerian degeneration is a series of complex changes in the distal nerve tissue after peripheral nerve injury, which is the basis and prerequisite for the regeneration of injured peripheral nerve 25,26 . With the progress of Wallerian degeneration, the damaged nerve myelin gradually deformed and fragmented until it was nally swallowed by macrophages.…”
Section: Spinal Cord Injury Delays Wallerian Degeneration Of the Scia...mentioning
confidence: 99%